Pocong: Contemporary Zombie Stories in Indonesia - Marina V. Frolova (Studia Litterarum)
The paper about the Indonesian “zombie” pocong examines specific features of the ghost stories in Indonesia, tracks the etymology of the words hantu (“ghost,” “undead”) and pocong (“wrapped in shroud”), and includes a translation of a typical ghost story (“Pocong and a Cart Hawker”). It introduces the hitherto understudied material in Russia that counts only a small number of Indonesian and Anglophone works. The aims of this paper include collecting data about this mythological creature from Indonesian sources, studying the image of pocong and contemporary narratives about him, searching his closest parallels in the world folklore, and interpreting the meanings of the character discovered in modern Indonesian culture. For religious people, pocong is a symbol of the frailty of life. Some traditional Muslims in modern Indonesia practice pocong related rituals (“Pocong’s oath,” pesugihan). Nowadays, the image of pocong is demythologized as it circulates in urban flesh-mobs, pranks, and horror films. The typology of this scary image is surprisingly similar not to Muslim genies but to from Chinese hopping vampires. Modern zombie studies shed light on the genealogy of pocong as a walking dead. Todd K. Platts discusses the spectrum of potential underpinnings of the zombie that include racism, terrorism, class inequality, disintegration of a nuclear family, consumer culture etc that may be applied to pocong as well. Pocong symbolizes oppressed common folk and this image is frequently used in mass political protests. Interpretation of pocong as a marginalized figure is relevant for the folklore studies in Indonesia, as well as for the study of horror-discourse in general.